Communication—Why High-Precision Coulometry and Lithium Plating Studies on Commercial Lithium-Ion Cells Require Thermal Baths. Issue 13 (26th August 2019) - Zülke, Alana; Li, Yi; Keil, Peter; Hoster, Harry
Abstract : We demonstrate how insufficient heat transport in environmental chambers compromises the meaningfulness of high-precision charge counting and leads to an underestimation of lithium plating in fast-charged lithium-ion batteries. Direct-contact liquid cooling of cylindrical cells excludes temperature fluctuations observed in thermal chambers and restricts self-heating to 2 K in comparison to the 14 K in thermal chambers, under 1.5 C-rate cycling. Our thermal-electrochemical model replicated well the experimental results. For high-precision coulometric studies to be meaningful and more comparable across different laboratories, especially for large-format and high-power cells, direct-contact cooling in thermal baths must become the new standard.